Measuring women’s empowerment and its impact on child development in African countries: an analysis of national surveys - Ewerling, Fernanda (2018)
The Sustainable Development Goals strongly focus on equity. Goal 5 explicitly aims to empower all women and girls, reinforcing the need to have a reliable indicator to track progress. Women’s empowerment has a strong potential to improve health and economic outcomes both in the households and communities. The first objective of this thesis was to develop a novel women’s empowerment indicator using Demographic and Health Survey (DHS) data from 34 African countries, broadening opportunities for monitoring and research on women’s empowerment in the region (paper 1). The proposed indicator, named Survey-based Women’s empowerment (SWPER), composed by 15 items, allows the assessment of three empowerment domains: attitude to violence, social independence and decision making. It allows withincountry and between-country comparison, as well as time trend analysis, which no other survey-based index provides. This indicator was then used to evaluate the association between women’s empowerment and the Composite Coverage Index (CCI), a weighted average of coverage with eight interventions in reproductive, maternal, newborn and child health (paper 2). We also assessed whether these effects are modified by wealth. Using DHS data for 36 countries, we found a positive association between the three SWPER domains and the CCI at country level. One standard deviation change in empowerment increased the CCI by 15 (attitude to violence and decision-making domains) and 23 percentage points (social independence). For the latter, the association was modified by wealth: each additional standard deviation was associated with 39.0 (95% CI: 26.2 – 51.9) percentage points increase in the CCI among the poorest and 9.7 (95% CI: 5.1 – 14.3) percentage points among the richest quintile. Also using the SWPER, we evaluated the effect of the mothers’ empowerment on the development on the child (paper 3). To do so, we used the Early Childhood Development Index, which allows the assessment of four developmental domains, namely literacynumeracy, physical, learning and socioemotional. On average, 14.3%, 92.0%, 80.4% and 65,7% of the children were on track for literacy-numeracy, physical, learning and socioemotional developmental domains, respectively. Overall, for each standard deviation increase in attitude to violence, social independence and decision-making scores, the odds for the child being on track on literacy-numeracy increased 31%, 90% and 31%, respectively. However, the mothers’ empowerment overall effects on the physical, learning and socialemotional development of the child was very small or null, which may be related to the low variability in these outcomes. Overall, our findings suggest that efforts toward the achievement of SDG5 (Achieve gender equality and empower all women and girls) may have an important impact on both maternal and child health, as well as on the development of the child in literacynumeracy on the African continent.